2023
DOI: 10.1021/acs.jproteome.3c00330
|View full text |Cite
|
Sign up to set email alerts
|

Direct Mass Spectrometry-Based Detection and Antibody Sequencing of Monoclonal Gammopathy of Undetermined Significance from Patient Serum: A Case Study

Abstract: Monoclonal gammopathy of undetermined significance (MGUS) is a plasma cell disorder characterized by the presence of a predominant monoclonal antibody (i.e., M-protein) in serum, without clinical symptoms. Here we present a case study in which we detect MGUS by liquid-chromatography coupled with mass spectrometry (LC-MS) profiling of IgG1 in human serum. We detected a Fab-glycosylated M-protein and determined the full heavy and light chain sequences by bottom-up proteomics techniques using multiple proteases, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The Uniprot reviewed human protein database was used, with ∼ 20300 entries (Release number 2018_05). An additional sequence of a dominant IGHG1 clone for P1 patient was added in the search, previously described by Peng et al 14 . All downstream analyses were carried out in R15.…”
Section: Methodsmentioning
confidence: 99%
“…The Uniprot reviewed human protein database was used, with ∼ 20300 entries (Release number 2018_05). An additional sequence of a dominant IGHG1 clone for P1 patient was added in the search, previously described by Peng et al 14 . All downstream analyses were carried out in R15.…”
Section: Methodsmentioning
confidence: 99%
“…The DeepNovo method, along with its successor method, PointNovo, has been incorporated into the commercial software PEAKS, and most of these 16 applications make use of that software. Among all 27 studies, the most common application is detection of neoantigens and noncanonical antigens [77,79,86,87,89,91,100,103], followed by antibody sequencing [84,88,99 Peptide assignments for the MS/MS spectrum from the nine-species benchmark data with universal spectrum identifier [104] mzspec:PXD003868:BY 04 heat 3:scan:28038. This spectrum is annotated as peptide "VFAIAN[+0.984]AFAK" in the original version of this dataset [1] but was reannotated as "VFAIANAFAK" recently [65].…”
Section: Applications Of Deep Learning De Novo Sequencing Methodsmentioning
confidence: 99%
“…Evaluating the tools on human and mouse antibody data, the authors concluded that Casanovo and PointNovo show improved peptide recall across different enzymes and datasets compared with competing methods. Second, Tran et al [76] have evaluated PEAKS, PointNovo, Casanovo, and GraphNovo on five datasets: human tryptic data, Method Year Application Ind DeepNovo 2020 Detection of neoantigens [77] 2021 De novo sequencing in metaproteomics [78] ✓ 2021 Detection of neoantigens [79] ✓ 2021 Detection of junction peptides [80] ✓ 2021 Detection of shell proteins [81] ✓ 2023 Detection of neuropeptides [82] ✓ 2023 Detection of proteasome-generated spliced and non-spliced peptides [83] ✓ 2023 Antibody sequencing [84] ✓ 2023 Detection of short peptides [85] ✓ 2023 Noncanonical antigen detection [86] ✓ 2023 Detection of neoantigens [87] 2024 Antibody sequencing [88] ✓ 2024 Detection of neoantigens [89] 2024 Detection of venom proteins [ ✓ 2022 Detection of neoantigens [103] ✓ Table 3: Applications of deep learning de novo sequencing methods. The final column ("Ind") indicates whether the application was published independently of the original authors of the work.…”
Section: Performance Comparisonsmentioning
confidence: 99%
“…To make this antibody available for general use, we set out to determine its sequence based on the available hybridoma-derived product. Recently, we have reported a method to reverse-engineer monoclonal antibodies by determining the sequence directly from the purified protein product based on liquid chromatography coupled to mass spectrometry (LC-MS), using a bottom-up proteomics approach ( 21 , 22 , 23 , 24 ). Here, we applied this method to obtain the full sequence of 139H2.…”
Section: Introductionmentioning
confidence: 99%